2016
DOI: 10.1073/pnas.1602196113
|View full text |Cite
|
Sign up to set email alerts
|

Rating antifreeze proteins: Not a breeze

Abstract: Antifreeze proteins (AFPs) are an interesting class of biomolecules that hinder macroscopic freezing by binding to small ice crystals and blocking their further growth. They were first discovered in the 1960s in arctic fish (1) and have since been observed in a wide range of other organisms, e.g., bacteria (2), fungi (3), plants (4), insects (5), and vertebrates (1,6), that live in low-temperature environments. AFPs are also of considerable practical interest due to their potential applications in cryopreserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…As TH activity is concentration dependent, 77 ζ = (hMP – hFP)/√ C AF(G)P has been introduced as a quantitative measure for TH activity. 66 , 78 Maximal TH activities measured by cryoscopy range from 0.1–0.5 °C in apoplastic extracts from overwintering plants 4 , 61 and ∼2 °C for 30–40 g L –1 protein in fish serum 21 , 74 to ∼2 to 13 °C for 10-times lower concentrations in insect hemolymph. 54 TH activity can be improved upon addition of (sub)molar concentrations of small molecular solutes 79 and ions, 20 , 80 conjugation 81 to or complexation 82 with potentiating proteins 82 or other ice-binding proteins 81 and polymers, 83 , 84 and IBS enlargement.…”
Section: Ibp Activitymentioning
confidence: 99%
“…As TH activity is concentration dependent, 77 ζ = (hMP – hFP)/√ C AF(G)P has been introduced as a quantitative measure for TH activity. 66 , 78 Maximal TH activities measured by cryoscopy range from 0.1–0.5 °C in apoplastic extracts from overwintering plants 4 , 61 and ∼2 °C for 30–40 g L –1 protein in fish serum 21 , 74 to ∼2 to 13 °C for 10-times lower concentrations in insect hemolymph. 54 TH activity can be improved upon addition of (sub)molar concentrations of small molecular solutes 79 and ions, 20 , 80 conjugation 81 to or complexation 82 with potentiating proteins 82 or other ice-binding proteins 81 and polymers, 83 , 84 and IBS enlargement.…”
Section: Ibp Activitymentioning
confidence: 99%
“…F reezing of water into ice is ubiquitous in nature and can occur in a wide range of environments, from biological cells (1) and soil (2) to meteors (3) and atmospheric clouds (4). Ice formation is particularly important in the atmospheric processes that exert a major influence on our weather and climate.…”
mentioning
confidence: 99%
“…The most important factor is the specific arrangement of especially threonines. Further studies [89][90][91] on this issue showed more than two planes of ice that IBPs may bind to, and these were basal, primary prism, secondary prism, and pyramidal prism. The plurality of these planes caused different values of TH activity measured by cryoscopy and sonocrystallization in six examined AFPs of various origins bound to the ice faces specific for them.…”
Section: Antifreeze Activities Of Afpsmentioning
confidence: 99%